Reduction of quality as evidenced by texture profile analysis of cooled and frozen rasogolla during low temperature storage - Agrawala, Ashok Kumar; Sinha, Geetesh (Indian Journal of Dairy Science, 2016)
The texture of rasogolla is of great importance in its quality and acceptability. It is dependent on the manufacturing process and storage conditions. In the present investigation, samples of rasogolla balls were purchased from a popular vendor who had a reputation of maintaining uniform quality. Sugar syrup from rasogolla balls was drained on a perforated stainless steel plate for 15 min and then transferred to polystyrene cups. First lot of rasogolla was stored at normal refrigerator temperature (5oC), second lot was at 0oC and third lot was at freezer temperature (-15oC). Another two lots of rasogollas, individual quick frozen upto -50 and 0oC, were also subjected to storage at -15 and 0oC respectively. Before textural analysis, stored rasogolla were thawed to room temperature by the addition of sugar syrup @ 25 ml per ball. The tempered rasogolla balls were drained for 15 min on a perforated stainless steel plate and cut with into 20Ã—20Ã—20 mm cubes. The changes in rheological characteristics of normally and individually quick frozen rasogolla kept at different temperatures were determined every week. The characteristics like hardness, adhesive force, cohesiveness, adhesiveness, springiness, gumminess and chewiness were determined. It was found that all types of rasogollas were generally became more harden, adhesive, gummy and chewy and lesser cohesive and springy when subjected to storage at low temperatures. The rheological parameters of relaxation and retardation times were also found decreasing. These quality losses were observed in all types of rasogolla but it was found less which was stored at -15oC as compared to those at 0 and 5oC.